2016
DOI: 10.1039/c5sc02857d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of primary azides to aldehydes catalyzed by active site variants of myoglobin

Abstract: Engineered variants of myoglobin can efficiently catalyze the conversion of primary azides to aldehydes in water and at room temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 64 publications
5
37
0
1
Order By: Relevance
“…To this end, we characterized and compared the catalytic activity and selectivity of a set of single and double reversion mutants in the reaction with phenyl allyl sulfide ( 1 ) and EDA (SI Table S2). In line with our previous observations, [3d, 9a, 16] mutation of the distal His residue (H64V) increases both the TTN (2,230 vs. 1,615 for Mb) and product formation rate (121 vs. 79 min −1 ), possibly through facilitating access of the substrate to the heme cavity (SI Figure S1). The L29S mutation further enhances the catalytic competency of the hemoprotein, as suggested by the increased total turnovers (3,085 TTN) supported by Mb(L29S,H64V).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…To this end, we characterized and compared the catalytic activity and selectivity of a set of single and double reversion mutants in the reaction with phenyl allyl sulfide ( 1 ) and EDA (SI Table S2). In line with our previous observations, [3d, 9a, 16] mutation of the distal His residue (H64V) increases both the TTN (2,230 vs. 1,615 for Mb) and product formation rate (121 vs. 79 min −1 ), possibly through facilitating access of the substrate to the heme cavity (SI Figure S1). The L29S mutation further enhances the catalytic competency of the hemoprotein, as suggested by the increased total turnovers (3,085 TTN) supported by Mb(L29S,H64V).…”
supporting
confidence: 92%
“…Previously, we found that mutations at these positions can dramatically alter the activity and selectivity of Mb variants as carbene [3d, 7, 9, 16] and nitrene [17] transfer catalysts. Upon testing in the reaction with 1 and EDA, a number of Mb variants with significantly improved catalytic activity compared to the wild-type protein were identified (Figure S3).…”
mentioning
confidence: 99%
“…Giovani et al have shown that engineered myoglobins can catalyze the oxidative deamination of benzylic azides to yield aldehydes [37•], providing a biocatalytic alternative for aldehyde synthesis by alcohol oxidation with chromium- or manganese-based reagents. Myoglobin variant Mb(H64V,V68A) converted a broad range of primary azides to the corresponding aldehydes with up to 89% yield, exhibiting between 100- and 1000-fold higher catalytic activity than previously reported synthetic catalysts.…”
Section: Nitrene Transfer Reactions Catalyzed By Engineered Hemoproteinsmentioning
confidence: 99%
“…While not involving a heme enzyme, this reaction was proposed to involve catalytic intermediates that are reminiscent of those implicated in hemoprotein-catalyzed nitrene C–H insertion [11] and azide oxidation [37•]. …”
Section: Nitrene Transfer Reactions Catalyzed By Engineered Hemoproteinsmentioning
confidence: 99%
“…They have developed several target chemical transformations that are synthetically valuable to organic synthesis methodology. In the last two years, their group has shown significantly enhanced reactivity towards olefin cyclopropanation [55], provided the first biocatalytic example of the conversion of primary azides to aldehydes [56], carbene N-H and S-H insertion [57,58], and olefination of aldehydes by fine-tuning the active site with larger and smaller apolar residues within the protein scaffold of myoglobin [59].…”
Section: Some Recent Examples Of the Versatility Of Myoglobin Mutantsmentioning
confidence: 99%